2014
DOI: 10.1002/cctc.201402793
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Surface Properties and Catalytic Performances of Pt–Ru Bimetallic Nanoparticles by Thermal Treatment

Abstract: The surface structure and catalytic properties of Pt–Ru bimetallic catalysts with identical bulk composition can be continuously tuned by treatment at different temperatures. The activity of these catalysts in CO oxidation was positively related to the treatment temperature, but the opposite trend was observed for the solvent‐free oxidation of benzyl alcohol. It was found that migration of Pt to the surface occurred when the treatment temperature was increased. During this process, the surface of the Pt–Ru nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…However, higher calcination temperature might remove most of the residual plant biomass, which made the active species prone to agglomeration. On the other hand, the results was similar to that of the Pt–Ru/C reported by Zhang, who found that the activity decline predictably as increasing the treatment temperature. Higher treatment temperature could lead to more oxidized Pt species which was less active compared with the metallic Pt to provide hydrogen adsorption and dissociation site.…”
Section: Resultssupporting
confidence: 89%
“…However, higher calcination temperature might remove most of the residual plant biomass, which made the active species prone to agglomeration. On the other hand, the results was similar to that of the Pt–Ru/C reported by Zhang, who found that the activity decline predictably as increasing the treatment temperature. Higher treatment temperature could lead to more oxidized Pt species which was less active compared with the metallic Pt to provide hydrogen adsorption and dissociation site.…”
Section: Resultssupporting
confidence: 89%
“…In the literature, composition-induced structural changes , were shown for Pt–Ru nanoalloys and mixed structures were obtained at low temperatures. Nevertheless, a high-temperature treatment after synthesis showed Pt segregation to the surface, leading to “core-shell” particles and it has been shown that core–shell Ru@Pt nanoalloys have higher catalytic activity for CO oxidation than mixed Ru–Pt nanoparticles …”
Section: Introductionmentioning
confidence: 99%
“…What is even worse is that, as indicated previously, the widely used metal oxide supports (i.e., ceria) always work as electron acceptors, making the complexation even easier. Our results indicated that the C support can give electrons to Pt and Cu metals to compensate the electron loss, , but carbon has no ability to activate and transfer oxygen to metal nanoparticles. Thus, what if we combine carbon and CeO 2 to take the advantage of both?…”
Section: Introductionmentioning
confidence: 79%
“…What is even worse is that, as indicated previously, the widely used metal oxide supports (i.e., ceria) always work as electron acceptors, making the complexation even easier. Our results indicated that the C support can give electrons to Pt and Cu metals to compensate the electron loss, 23,24 ■ RESULTS AND DISCUSSION Catalyst Preparation. The CeO 2 /C was prepared by the impregnation method with calcination (Supporting Information) to ensure the interaction between C and CeO 2 .…”
Section: ■ Introductionmentioning
confidence: 93%
See 1 more Smart Citation